2022
DOI: 10.3390/genes13010120
|View full text |Cite
|
Sign up to set email alerts
|

LRP6 Receptor Plays Essential Functions in Development and Human Diseases

Abstract: LRP6 is a member of the low-density lipoprotein receptor superfamily of cell-surface receptors. It is required for the activation of the Wnt/β-catenin signalling pathway. LRP6 is detected in different tissue types and is involved in numerous biological activities such as cell proliferation, specification, metastatic cancer, and embryonic development. LRP6 is essential for the proper development of different organs in vertebrates, such as Xenopus laevis, chickens, and mice. In human, LRP6 overexpression and mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 72 publications
2
14
0
Order By: Relevance
“…Other reports showed that during development components of the FGF, Wnt, Notch, BPM, and Hedgehog signaling orchestrate crucial cellular events including proliferation, migration, differentiation, epithelial-mesenchymal transition (EMT), morphogenesis and somite myogenesis patterning. When gene expression controlling these events is dysregulated, it leads to disease induction ( Hansson et al, 2004 ; Logan and Nusse, 2004 ; Ma et al, 2010 ; Teven et al, 2014 ; Xiao et al, 2017 ; Abreu de Oliveira et al, 2022 ; Alrefaei and Abu-Elmagd, 2022 ; Towler and Shore, 2022 ). Although our RT did not receive microRNA-related manuscripts, it is well-established that microRNAs play an important role in physiology and disease ( Sayed and Abdellatif, 2011 ; Bhaskaran and Mohan, 2014 ; Kalayinia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other reports showed that during development components of the FGF, Wnt, Notch, BPM, and Hedgehog signaling orchestrate crucial cellular events including proliferation, migration, differentiation, epithelial-mesenchymal transition (EMT), morphogenesis and somite myogenesis patterning. When gene expression controlling these events is dysregulated, it leads to disease induction ( Hansson et al, 2004 ; Logan and Nusse, 2004 ; Ma et al, 2010 ; Teven et al, 2014 ; Xiao et al, 2017 ; Abreu de Oliveira et al, 2022 ; Alrefaei and Abu-Elmagd, 2022 ; Towler and Shore, 2022 ). Although our RT did not receive microRNA-related manuscripts, it is well-established that microRNAs play an important role in physiology and disease ( Sayed and Abdellatif, 2011 ; Bhaskaran and Mohan, 2014 ; Kalayinia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of LRP5 and LRP6 has been associated with various diseases ranging from bone, cardiac, neurodegenerative, diabetes, and hypercholesterolemia to cancer. Though impaired LRP6 signaling is associated with human diseases, studies suggest a predominant role of LRP6 during development, where loss-of-function of LRP6 in mice was embryonically lethal [62][63][64][65].…”
Section: The Lrp Familymentioning
confidence: 99%
“…Furthermore, there is a 98% amino acid sequence similarity between human and mouse LRP6. Furthermore, at the protein level, LRP6 shares more than 93% identity with humans and chickens [63].…”
Section: Evolution Of Lrp5/6mentioning
confidence: 99%
“…The Wnt co-receptor Lrp6 acts upstream of β-catenin in the canonical pathway and is required for a wide range of processes pertaining to embryogenesis and organogenesis, including neural tube closure ( Alrefaei and Abu-Elmagd, 2022 ; Carter et al, 2005 ; He et al, 2004 ; Kokubu et al, 2004 ; Mao et al, 2001 ; Pinson et al, 2000 ; Song et al, 2009 , 2010 ; Tamai et al, 2000 ; Wang et al, 2016 ; Wehrli et al, 2000 ; Zhou et al, 2008 , 2004 , 2010 ). Multiple studies have identified mutations in human LRP6 gene from patients with NTDs ( Allache et al, 2014 ; Lei et al, 2015 ; Shi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%